2003
DOI: 10.1007/s00442-003-1184-9
|View full text |Cite
|
Sign up to set email alerts
|

Host plant effects on parasitoid attack on the leaf beetle Chrysomela lapponica

Abstract: Larvae of the leaf beetle Chrysomela lapponica obtain salicyl glucosides (SGs) from the host plant to produce a defensive secretion with salicylaldehyde. In northern Russia, larvae and pupae experience high parasitism by the phorid fly Megaselia opacicornis and tachinid fly Cleonice nitidiuscula. We compared the suitability of the SG-rich Salix borealis and SG-poor S. caprea and S. phylicifolia to Ch. lapponica and tested whether enemy pressure on Ch. lapponica varies among host species that differ in SG conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 62 publications
3
36
0
Order By: Relevance
“…Parasitism by M. opacicornis is spatially density dependent, which suggests that this parasitoid may use chemical cues to locate prey from a distance (Zvereva and Kozlov 2000). In addition, Zvereva and Rank (2003) recently demonstrated that M. opacicornis parasitism and oviposition was greater on beetles on SG-rich host species than on beetles on SG-poor species (Zvereva and Rank 2003). These results indicate that the beetle's defensive secretion attracts M. opacicornis for prey location and oviposition.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Parasitism by M. opacicornis is spatially density dependent, which suggests that this parasitoid may use chemical cues to locate prey from a distance (Zvereva and Kozlov 2000). In addition, Zvereva and Rank (2003) recently demonstrated that M. opacicornis parasitism and oviposition was greater on beetles on SG-rich host species than on beetles on SG-poor species (Zvereva and Rank 2003). These results indicate that the beetle's defensive secretion attracts M. opacicornis for prey location and oviposition.…”
Section: Introductionmentioning
confidence: 85%
“…The pupal parasitoid Megaselia opacicornis Schmitz (Diptera, Phoridae) causes up to 40% mortality in natural populations of Ch. lapponica in NW Russia and Finnish Lapland (Zvereva and Kozlov 2000;Zvereva and Rank 2003). Parasitism by M. opacicornis is spatially density dependent, which suggests that this parasitoid may use chemical cues to locate prey from a distance (Zvereva and Kozlov 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Why have there been so few studies documenting EFS (12,(18)(19)(20)(21)? Only three studies have satisfactorily established the occurrence of EFS, but they have been agricultural systems (22,23) or artificial host shifts (24).…”
Section: Figmentioning
confidence: 99%
“…These effects can strongly vary among plant species (Smith 1957;Altahtawy et al 1976;Bhatt & Singh 1989;Senrayan & Annadurai 1991;Werren et al 1992;Fox et al 1996;Kruse & Raffa 1997;Eben et al 2000;Harvey et al 2003;Zvereva & Rank 2003;Lu et al 2004) and even among cultivars of a same plant species (Kauffman & Flanders 1985;Orr & Boethel 1985;Hare & Luck 1991;Reed et al 1991;Rogers & Sullivan 1991;Riggin et al 1992;Stark et al 1992;Dosdall & Ulmer 2004;KahuthiaGathu et al 2008).…”
Section: Introductionmentioning
confidence: 99%